Zika virus challenges for neuropsychiatry - Simões e Silva AC (Dove Medical Press, 2016)
Ana Cristina Simões e Silva,1,2 Janaina Matos Moreira,1,2 Roberta Maia Castro Romanelli,2 Antonio Lucio Teixeira1,3 1Interdisciplinary Laboratory of Medical Investigation, 2Department of Pediatrics, Faculty of Medicine, Federal University of Minas Gerais (UFMG), Belo Horizonte, Brazil; 3Neuropsychiatry Program, Department of Psychiatry and Behavioral Sciences, McGovern Medical School, University of Texas Health Science Center at Houston, Houston, TX, USA Abstract: Before 2007, Zika virus (ZIKV) was generally considered as an arbovirus of low clinical relevance, causing a mild self-limiting febrile illness in tropical Africa and Southeast Asia. Currently, a large, ongoing outbreak of ZIKV that started in Brazil in 2015 is spreading across the Americas. Virus infection during pregnancy has been potentially linked to congenital malformations, including microcephaly. In addition to congenital malformations, a temporal association between ZIKV infection and an increase in cases of Guillain–Barré syndrome is currently being observed in several countries. The mechanisms underlying these neurological complications are still unknown. Emerging evidence, mainly from in vitro studies, suggests that ZIKV may have direct effects on neuronal cells. The aim of this study was to critically review the literature available regarding the neurobiology of ZIKV and its potential neuropsychiatric manifestations. Keywords: Zika virus, microcephaly, Guillain–Barré syndrome, neurodevelopmental disorders